(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article provides detailed information about the organization of extracurricular activities in geography lessons. Educational work in secondary school is limited to the program and, within the specified time, geography lessons consist of organizing and conducting extracurricular activities.